Future Technological Education Developing Professional Skills for Teachers (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses different approaches to defining the concepts of “competence”, “competence”, and “competency-oriented education” in the scientific and pedagogical literature. The article reveals the basic rules of competency-oriented training of future primary school teachers in the university environment. The author discusses different approaches to the definition of “competency-based education” in the scientific and educational literature. The article describes the basic rules of competency-based education of future primary school teachers. The main analysis is the views and comments on the development of professional skills of future teachers of technological education, first of all, to improve their skills and abilities.